2014
DOI: 10.5194/hess-18-3571-2014
|View full text |Cite
|
Sign up to set email alerts
|

Historical land-use-induced evapotranspiration changes estimated from present-day observations and reconstructed land-cover maps

Abstract: Abstract. Recent results from the LUCID model intercomparison project have revealed large discrepancies in the simulated evapotranspiration (ET) response to the historical landuse change. Distinct land-surface parameterizations are behind those discrepancies, but understanding those differences rely on evaluations using still very limited measurements. Model benchmarking studies with observed ET are required in order to reduce the current uncertainties in the impacts of land use in terrestrial water flows. Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 52 publications
2
28
0
Order By: Relevance
“…Our results suggest that the CLM represents the observed changes in R net and G well, but there remain issues in simulating the energy partitioning between LE and H , which also further confirms the large uncertainties in simulated ET responses to LULCC revealed in several recent studies (e.g., Pitman et al, 2009;Boisier et al, 2012Boisier et al, , 2014de NobletDucoudré et al, 2012;Vanden Broucke et al, 2015). Based on the observations, deforestation generally leads to a decrease in summer daytime R net , accompanied by decreased LE and H .…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Our results suggest that the CLM represents the observed changes in R net and G well, but there remain issues in simulating the energy partitioning between LE and H , which also further confirms the large uncertainties in simulated ET responses to LULCC revealed in several recent studies (e.g., Pitman et al, 2009;Boisier et al, 2012Boisier et al, , 2014de NobletDucoudré et al, 2012;Vanden Broucke et al, 2015). Based on the observations, deforestation generally leads to a decrease in summer daytime R net , accompanied by decreased LE and H .…”
Section: Discussionsupporting
confidence: 69%
“…Information about the variables used from FLUXNET2015. The marginal distribution sampling (MDS) filling method is based on Reichstein et al (2005), and the ERA-Interim filling method can be found in Vuichard and Papale (2015 ration (ET), and land surface temperature changes due to historical LULCC (Boisier et al, , 2014 and the climatic effects of forest (Li et al, 2015). Meanwhile, the development of FLUXNET (Baldocchi et al, 2001) enables the study of land surface responses to different land-cover types based on paired field observations from neighboring flux towers over forest and open land (Juang et al, 2007;Lee et al, 2011;Luyssaert et al, 2014;Teuling et al, 2010;Williams et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The replacement of natural vegetation also changes ET (Boisier et al, 2014) and LST because the surface biophysical variables (i.e. surface albedo, LST, emissivity and indirectly leaf area index (LAI) and normalized difference vegetation index (NDVI)) are interconnected through the surface radiation balance.…”
Section: Introductionmentioning
confidence: 99%
“…On a regional scale, similar conclusions are reached by Haddeland et al (2007) for North America and Asia, with the largest land-cover-induced changes in runoff occurring over Southeast Asia. Hence, despite large variations amongst studies concerning the actual amount and spatial variation of evapotranspiration and runoff changes due to land cover change, related, for example, to uncertainties in evapotranspiration reconstructions, models and land cover maps (Boisier et al, 2014), land cover change is overall thought to have reduced global evapotranspiration and increased runoff to an extent that is at least of similar magnitude to the impact of climate change or other anthropogenic impacts such as irrigation.…”
Section: Introductionmentioning
confidence: 99%